Deployment of protein ontology framework - Sidhu, Amandeep; Dillon, Tharam S.; Chang, Elizabeth (Sathyabama University, Chennai, 2007)
Bioinformatics researchers have long identified the need for interoperation among protein databases knowledge bases and other information sources. Despite advances, interoperation among knowledge and data sources is still an issue with every new protein data and information source that is created. We proposed Protein Oncology (PO) in 2003 (see: http://www.proteinontology/info/) that provides an efficient integration and interoperation framework among existing protein data and information sources. In this paper we explore its design, current issue its development, and its growing adoption as a standard for representation in biomedical domain.